THE GROWTH OF PATIN FISH (Pangasiushypophthalmus )USING AQUAPONIC SYSTEMS WITH DIFFERENT PLANTS - Leonardo Davinci; Mulyadi Mulyadi; Sukendi Sukendi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT The aquaponics system is a combination of fish rearing with plant maintenance. With this aquaponics model, two products are obtained at once, namely vegetables and fresh fish. The advantages of this system are found in the reuse of water which is a living medium for fish and water simultaneously. In addition, the use of narrow land with the application of aquaponics for catfish cultivation can be used as a solution for the production of home-scale foodstuffs and improve local food security. The purpose of this study was to determine the effectiveness of a combination of common vegetable crops consumed in the growth of catfish (Pangasius hypophthalmus) in an aquaponics system. The types of vegetable plants used in this study include basil, mustard greens, lettuce and kale. The  prameters meaned the research include of the absolute weight growth rate, the specific growth rate and absolute length growth. The best results are shown by the use of mustard plants, followed by a combination of lettuce, basil and kale. The best treatment in this study was treatment with mustard plants, with absolute weight growth of 22.5 g, absolute length growth of 5.24 cm, specific growth rate of 15.03%, and feed conversion of 1.17. respectively Maintenance of the aquaponics system with different types of plant treatment showed the best survival rate of 100% in all treatments.Key words: aquaponics, catfish, basil, mustard greens, lettuce, kale, combination and food.